HIPNORELAKSASI MENURUNKAN TEKANAN DARAH DAN NADI PADA PASIEN PRE OPERASI FRAKTUR EKSTREMITAS - Martsiwi, Nika; Subiyanto, Paulus (Jurnal Media Ilmu Kesehatan, 2013)
Background: Preoperative patients can be experience an anxiety. Anxiety can be expressed through physiological changes that will be known by a change in the sympathetic response which some of them are increased in heart rate and blood pressure. Preliminary study results shows 4 of 6 patients got an increase in anxiety with signs of increased in blood pressure and pulse. Hypno relaxation is a complementary therapy for anxiety, while in the hypnotic state, most people will be experience relaxation, decrease blood pressure, and pulse. Objective: Determine the influence of hypno relaxation to the blood pressure and pulse in patients with preoperative fracture in RSUD Bantul. Methods: This study is a quassy experiment with design of the study is pre-test and post-test non equivalent control group. Samples were taken using purposive sampling techniques amounted to 24 respondents. 12 people was on control group and 12 was on intervention group. Research instrument which used was a record of hypno relaxation stages, the mercury sphygmomanometer and stethoscope. The results were analyzed using Independent Samples t-test and Paired Samples t-test. Results: The results of the equal measurement in blood pressure and pulse in the pre and post test control group are 1.17 x / min and 0.5 mmHg, which showed an increase. Whereas in the intervention group difference in equal blood pressure and pulse are 7.00 mmHg and 6.25 x / min, which showed a decrease. Statistic result using independent t-test got (p) value 0.000 <0.05 with t -7,257 for blood pressure and t -8,888 for pulse, and can be concluded that there is a significant difference in the mean value of pulse and blood pressure between the control group and intervention group of hypno relaxation. On the statistic test using Paired t-test got (p) value 0.000 <0.05 in the intervention group, it means that hypno relaxation can be influence the pulse and blood pressure significantly. Conclusion: Hypno relaxation have an effects on blood pressure and pulse on the preoperative patient's with fracture in RSUD Bantul. Keywords: Blood pressure, pulse, preoperative, fracture, and hypno relaxation.